1973
DOI: 10.1128/aac.3.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Nocardia asteroides to 45 Antimicrobial Agents In Vitro

Abstract: A method for preparing uniformly dispersed cultures of Nocardia asteroides for use in tests for susceptibility to antimicrobial agents is described. The minimal inhibiting concentration (MIC) of 45 agents for cultures thus prepared was determined with the use of a replica-inoculating apparatus. Minocycline at a concentration of 3.1 mug or less/ml inhibited 90% of the strains tested, and all were inhibited by 6.3 mug/ml. An erythromycin concentration of 0.8 mug or less/ml inhibited 40% of the strains, but the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
0

Year Published

1974
1974
2004
2004

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 8 publications
6
42
0
Order By: Relevance
“…Confirming the observations of Wilson and Williams (13), we found ampicillin to be the most active of the currently available penicillins and cephalosporins, but only less than half of the strains tested were inhibited by 25 Mg/ml in the first two tests, and the MICs of ampicillin in the third test were 50 to 200 ig/iml for most of the strains at 48 and 72 h. As previously shown by Sanford and co-workers (9), we also found erythromycin to be active in low concentrations against a large proportion of strains, but many of them required higher concentrations or were not inhibited by 100 ,g of that antibiotic per ml (2). Considering differences in media, time of incubation (48 h in most instances), and the differences in the sources and maintenance of the organisms tested by different workers, the results have been reasonably consistent and compatible with those presented here with respect to the individual antibiotics.…”
Section: Resultssupporting
confidence: 61%
“…Confirming the observations of Wilson and Williams (13), we found ampicillin to be the most active of the currently available penicillins and cephalosporins, but only less than half of the strains tested were inhibited by 25 Mg/ml in the first two tests, and the MICs of ampicillin in the third test were 50 to 200 ig/iml for most of the strains at 48 and 72 h. As previously shown by Sanford and co-workers (9), we also found erythromycin to be active in low concentrations against a large proportion of strains, but many of them required higher concentrations or were not inhibited by 100 ,g of that antibiotic per ml (2). Considering differences in media, time of incubation (48 h in most instances), and the differences in the sources and maintenance of the organisms tested by different workers, the results have been reasonably consistent and compatible with those presented here with respect to the individual antibiotics.…”
Section: Resultssupporting
confidence: 61%
“…Many in vitro studies of the sensitivities of Nocardia to antimicrobials have been reported; however, in most of them the investigators have used N. asteroides or other Nocardia species as the test organism or have included few (n Ͻ 20) N. brasiliensis strains (2,3,4,5,29,31,34,35). In the present work we studied the sensitivities of local N. brasiliensis strains to a wide range of antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
“…Only minocycline and amikacin are active against >90%o of strains (1,8), and both of these drugs have potential toxicities. Cefamandole is unlike--ly, however, to be useful in treating diseases of the central nervous system.…”
Section: Resultsmentioning
confidence: 99%